2000
DOI: 10.1128/aem.66.12.5273-5281.2000
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of PCR Fingerprinting, Infrequent-Restriction-Site PCR, and Pulsed-Field Gel Electrophoresis, Combined with Computerized Gel Analysis, in Library Typing of Salmonella enterica Serovar Enteritidis

Abstract: Strains of Salmonella enterica (n ‫؍‬ 212) of different serovars and phage types were used to establish a library typing computerized system for serovar Enteritidis on the basis of PCR fingerprinting, infrequent-restrictionsite PCR (IRS-PCR), or pulsed-field gel electrophoresis (PFGE). The rate of PCR fingerprinting interassay and intercenter reproducibility was low and was only increased when DNA samples were extracted at the same time and amplified with the same reaction mixtures. Reproducibility of IRS-PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 37 publications
1
38
0
1
Order By: Relevance
“…Pulsed-field gel electrophoresis (PFGE) and antimicrobial susceptibility typing (AST) are two commonly used methods for studying microbial epidemiology and trends in the antibiotic resistance of bacteria. PFGE is currently used by the CDC PulseNet surveillance program and is generally accepted as the "gold standard" for molecular typing of Salmonella (7,18,34,41,57). Due to its limitations, many studies have compared PFGE to other genetic typing methods in attempts to identify more powerful tools for epidemiological investigations and evolutionary analyses.…”
mentioning
confidence: 99%
“…Pulsed-field gel electrophoresis (PFGE) and antimicrobial susceptibility typing (AST) are two commonly used methods for studying microbial epidemiology and trends in the antibiotic resistance of bacteria. PFGE is currently used by the CDC PulseNet surveillance program and is generally accepted as the "gold standard" for molecular typing of Salmonella (7,18,34,41,57). Due to its limitations, many studies have compared PFGE to other genetic typing methods in attempts to identify more powerful tools for epidemiological investigations and evolutionary analyses.…”
mentioning
confidence: 99%
“…Consequently, PFGE has become a very important tool in epidemiology (14). Garaizar et al (9) and Ridley et al (14) used PFGE and computerized gel analysis to identify strains within Salmonella enterica serovar Enteritidis. They concluded that with standardization, PFGE protocols and results were reproducible among different laboratories.…”
mentioning
confidence: 99%
“…Serotyping, based on the Kauffmann-White scheme, remains the standard for classification of Salmonella isolates in outbreak investigations but now has been supplemented by a range of molecular genotyping methods [1,2]. In recent years, molecular-based techniques, such as PulsedField Gel Electrophoresis (PFGE), Restriction Fragment Length Polymorphism (RFLP), Random Amplified Polymorphic DNA (RAPD), Automatic Ribo-typing, rep-PCR, Multi-Locus Sequence Typing (MLST) have been shown to be useful methods for discrimination among isolates of pathogens [3,4]. Molecular-typing methods including rep-PCR, Multi-Locus Sequence Typing (MLST) have been shown to be useful methods for discrimination among isolates of pathogens [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, molecular-based techniques, such as PulsedField Gel Electrophoresis (PFGE), Restriction Fragment Length Polymorphism (RFLP), Random Amplified Polymorphic DNA (RAPD), Automatic Ribo-typing, rep-PCR, Multi-Locus Sequence Typing (MLST) have been shown to be useful methods for discrimination among isolates of pathogens [3,4]. Molecular-typing methods including rep-PCR, Multi-Locus Sequence Typing (MLST) have been shown to be useful methods for discrimination among isolates of pathogens [3,4]. Recent advances in molecular techniques have generated several typing methods based on PCR for genetic assessment of genetic relatedness of bacterial or fungal strains.…”
Section: Introductionmentioning
confidence: 99%